Dampak Ekonomi Akibat Wanprestasi Debitur di Bank Perkreditan Rakyat (BPR) - Rolando Marpaung; Micael Jeriko Damanik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
In a developing country, the role of credit has a fairly dominant role in developing economic potential. In this study, researchers formulate the problem as follows: What is the economic impact of debtor defaults on problem loans, What are the policies of financial institutions in dealing with debtor defaults in Rural Banks. Methods of library research, UU No.10 Tahun 1998 tentang Perbankan, Keppres No. 56 Tahun 2002 Tentang Restrukturisasi Kredit Usaha Kecil, dan Menengah, PBI Nomor: 7/3/PBI/2005 Tentang Batas Maksimum Pemberian Kredit Bank Umum dan KUH Perdata. Relationships that give rise to legal consequences guaranteed by law or law. If one party does not fulfill the rights and obligations voluntarily then one party can sue through the court. several policies in rescuing bad credit, and as for the things that are meant, namely: Rescheduling, Reconditioning, Restructuring. Impact of credit agreements, namely relationships that give rise to legal consequences guaranteed by law or law Economic impacts as a result of unfulfilled debtor achievements are as follows: Difficulties in Obtaining Loans from Other Financial Institutions, Higher Fines and Interests, Difficulties in Obtaining Credit Approval. Efforts made by BPR in the event of problem loans begin by negotiating and ending with legal channels.